PERAN JALALUDIN RAKHMAT SEBAGAI AKTOR DALAM PERJUANGAN HAK-HAK MINORITAS DI PARLEMEN - Hamdani Kurniawan; Ari Ganjar Herdiansah; Husin Muhammad Al-Banjari (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2021)
Minority groups often get discriminatory treatment from the surrounding socio-political environment .Therefore, They always fight for their right through political path. This study examines the role of an actor in fighting for the minorities’ right in parliament by highlighting the case of Jalaludin Rakhmat when he was a member of the House of Representatives Council in 2014-2019. The focus of this study is highlighting the political role of Jalaludin Rakhmat in fighting for the interests of the Syiah Group in the DPR, including describing the various dynamics along with it. The method used in this study is qualitative by collecting in depth-interview data with Jalaludin Rakhmat, several PDIP politicians, Syiah figures in West Java, and socio-political observers. The documents reading related to Jalaludin Rakhmat’s activities in both scientific journals and national news was also carried out to deepen the context and issues of Syiah in Indonesia. The results of this study revealed that Jalaludin Rakhmat’s role in legislative represents an actor-centered effort to intervene in the political process which aims to provide space for Syia groups to fulfill their various interests. However, from its political intervention efforts, it turned out that there were not many pro-Syia policy products.The success of Jalaludin Rakhmat’s intervention can not be determined only by the ability of the actor, but also by the political structure in the DPR. In addition, the identity attached to an actor also affects the success of his achievements in fulfilling his interests. Minority interest issues are still considered politically disadvantageous for political parties. This study concludes that minority actors who make it into parliament do not necessarily correlate with the opening of the political system to the struggle of minority groups.